'An interesting paper but not sufficiently theoretical': What does theorising in social research look like?. Issue 2 (July 2018) - Hammond, Michael
This article explores the concept of theorising in social research: what is theorising; how does theorising look to those doing it and how can it be explained as a practice. The article draws on different sources, including accounts of theory and theorising in the literature as well as first-hand reporting by academics. A view is reached of theorising as a personal undertaking involving a commitment to comprehend the world. It is argued that theorising is driven by the identification of interesting problems (practical or theoretical or both) and a motivation to solve them. Theorising involves a shift of awareness from subsidiary to focal and such a shift allows a more abstract level of understanding. Theorising tends to be an individual undertaking which draws on personal knowledge, but it is only made possible by psychological tools which have been handed down from the past, ones which need to be accessed, understood and adapted. Theorising requires a disciplined creativity in which the imagination is channelled into finding solutions that are compatible with observed data.